Self-assembled multilayer wrinkles on coated polymer surface - Wang, Bin; Ren, Jie; Ye, Yong-Hong (Micro & nano letters, 2014)
When coating different dielectrics on polymer surfaces, the surface morphology could be changed to wrinkles or cracks. The wrinkles or cracks are self-formed during the process of heating and cooling. The presented experimental results show that the wrinkles can be self-aligned between two nearest patterns. The direction of aligned wrinkles can be tuned to parallel, perpendicular and required degrees according to the different array-based patterns. The number of wrinkles can also be controlled by changing the size of the patterns. In a limited range, a larger size pit has more wrinkles.